ANALISIS PENGELOLAAN KEUANGAN UMKM BERBASIS LITERASI KEUANGAN: KAJIAN PUSTAKA UNTUK MENINGKATKAN KINERJA USAHA MIKRO - Kartijo; Nenden Hendayani; Andri Asmari; Dedi Karmana; Silvy Kartikasari; Machdi Sukmono (CV. Lafadz Jaya, 2026)
This article aims to analyse the financial management of MSMEs based on financial literacy through a literature review, in order to explain its role in improving the performance of micro-enterprises. Financial literacy is understood as the ability of business owners to understand, assess and apply financial knowledge in business activities, including recording transactions, budgeting, cash flow management, the use of finance, and investment decision-making. A number of studies indicate that financial literacy contributes positively to improving the quality of MSME financial management, particularly in terms of financial planning, cost control, debt management, and the formulation of more rational business strategies. Through a literature review approach, this article examines various previous research findings that discuss the relationship between financial literacy, financial management, and MSME performance. The findings indicate that financial literacy influences the performance of micro-enterprises both directly and indirectly through financial management behaviour, access to financial resources, and the financial self-confidence of business owners. Furthermore, sound financial management has been shown to support operational efficiency, enhance profitability, strengthen business sustainability, and help MSMEs adapt more effectively to changes in the business environment. Consequently, financial literacy can be positioned as a strategic foundation for strengthening the managerial capacity of MSMEs. This article emphasises the importance of practical, contextual and sustainable financial education programmes to enable micro-enterprises to improve the quality of their financial management and achieve more optimal business performance.